Draft Genome Sequence of Campylobacter ureolyticus Strain CIT007, the First Whole-Genome Sequence of a Clinical Isolate - Lucid, Alan (American Society for Microbiology, 2014)
Herein, we present the draft genome sequence of Campylobacter ureolyticus. Strain CIT007 was isolated from a stool sample from an elderly female presenting with diarrheal illness and end-stage chronic renal disease.